The Polish Version of the Resilience Scale 25: Adaptation and Preliminary Psychometric Evaluation - Konaszewski, Karol; Skalski, Sebastian; Surzykiewicz, Janusz (Frontiers in Psychology, 2021)
Background: The aim of the presented series of studies was to test the factor structure and assess the psychometric properties of the Resilience Scale 25 in the Polish population. It was developed and tested during the course of four independent studies analysing various aspects of the validation of the RS 25 questionnaire’s Polish version. Method: Study 1 concerned the procedure for developing the Polish language version. Study 2 (N = 2716) consisted of reliability tests and a confirmatory factor analysis. In Studies 3 (N = 733) and 4 (N = 431), the validity was assessed by examining the relationship between resilience and the assessment of ego-resiliency, the risk of depression, styles of coping with stress, perceived stress, and satisfaction with life. Results: The presented research results obtained using the measure indicate that it can be considered to be a reliable and valid research tool. A five-factor solution showed a good fit to the data: χ2/df = 12.85; RMSEA = .066 (low = .064; high = .068; 90% CI); GFI = .90; AGFI = .90. An assessment of the internal consistency was carried out on the basis of Cronbach’s alpha. The values achieved were satisfactory and indicate acceptable internal reliability of the questionnaire (0.89) and of the five dimensions: (1) purpose (0.65); (2) equanimity (0.65); (3) self-reliance (0.75); (4) perseverance (0.72); and (5) existential aloneness (0.66). In accordance with the predictions and earlier studies, resilience was correlated positively with ego-resiliency, a task-oriented style of coping with stress, and life satisfaction and negatively with perceived stress, the risk of depression, and an emotion-oriented coping style. Conclusion: The Polish version of the RS 25 allows the assessment of the intensity of resilience as a general indicator and its five constituting dimensions. Such a measurement seems to be important from the perspective of assessing the role of an individual’s resources in clinical psychology, health psychology, and psychotherapy